Pengaruh Leader Member Exchange, Kompetensi, dan Quality of Work Life Terhadap Kepuasan Kerja Karyawan - Eka Kurnia Saputra eka; Muhammad Muazamsyah muazamsyah; Andrian andrian; Octojaya Abriyoso octojaya; Muhammad Rizki rizki (Publikasi Indonesia, 2022)
With limited human resources, organizations are required and expected to be able to optimize them so that the organizational goals that have been set can be achieved. The purpose of this study is to analyze the effect of leader member exchange, competence, and quality of work life on employee job satisfaction at PT. BPR Central Sejahtera partially or simultaneously. This research uses associative quantitative research. Data collection techniques in this study were observation, questionnaires and literature study, this study used a saturated sample of 32 people. From the results of job satisfaction data analysis shows that there is a significant influence between the independent variables, namely leader member exchange, competence, and quality of work life on the dependent variable, namely job satisfaction, this is indicated by the t-count value of leader member exchange 4.639, the t-count value of competence 3.473, the t-count value of quality of work life is 5.023, which is greater than t-table 2.048. Y = 0.757 + 0.658 X1 + 0.275 X2 + 0.163 X3 + e. From the equation above, it can be seen that the independent variables that have the most influence on job satisfaction are leader member exchange compared to others, namely competence, and quality of work life.